An Exploratory Study of Students’ Indiscipline at Islamic University in Uganda - Hassan, Amina (East African Journal of Education Studies, 2021)
The study explored the common students’ indiscipline at Islamic University in Uganda. The study was quantitative and a cross-sectional survey design was used. The population of the study was 3,486 registered students in the academic year 2019/2020. They were selected from the Faculty of Education, Faculty of Management Studies, Faculty of Law, Faculty of Social Sciences, and Faculty of Science. A sample of 265 respondents was selected for the study using proportionate and random sampling. The mean score was computed to analyse the data. To conclude, the point range of the arithmetic mean was considered. The study found that the common indiscipline among learners in IUIU included disrespect to teachers and school rules and regulations, theft, and irregular attendance. The study recommended IUIU administration improves staff remuneration to change the status of the teachers. Furthermore, the administration needs to tighten security in the university and residents need to take care of their property to avoid theft. The researcher also recommended that a study should be carried out to find out the cause of students’ irregular attendance